2019
DOI: 10.1016/j.mmcr.2018.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus endocarditis diagnosed by fungemia plus serum antigen testing

Abstract: Fungal endocarditis remains an uncommon clinical diagnosis, though is likely to become more frequent due to the global increase in transplantations and cardiac valvular surgery. A case of prosthetic valve endocarditis due to Aspergillus fumigatus is described that was diagnosed with serologic fungal markers and confirmed with positive blood cultures, an uncommon finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…A review article that included 20 cases of AE showed that Aspergillus PCR test was positive in all cases, while BDG and GM were positive in 85.7% and 62.5% of cases, respectively. However, all three tests were negative in 20% of the cases [7] , [8] , [9] .…”
Section: Discussionmentioning
confidence: 93%
“…A review article that included 20 cases of AE showed that Aspergillus PCR test was positive in all cases, while BDG and GM were positive in 85.7% and 62.5% of cases, respectively. However, all three tests were negative in 20% of the cases [7] , [8] , [9] .…”
Section: Discussionmentioning
confidence: 93%
“…7 In cases of endocarditis with negative blood culture, for accurate and early diagnosis and ruling out fungal etiology, 1,3-β-D-glucans (BDG) and/or galactomannan (GM) are promising approaches for AE to initiate antifungal therapy prior to vulvar dysfunction, heart failure, and/or embolic phenomena. 18 As a cell-wall biomarker of Aspergillus, GM has been widely used to diagnose invasive aspergillosis in neutropenic patients. Since the GM antigen is cleared by neutrophils, its usage in non-neutropenic patients is limited, due to low diagnostic value and high likelihood of false-negative results.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies conducted by Erhlich [ 108 ] revealed that co-inoculation of AF − strains with AF + substantially reduced the production of AF in corn under in vitro conditions. The potential for biocontrol of AFs using AF − strains has been demonstrated under field conditions in cotton [ 109 ], peanuts [ 85 ], and corn [ 97 , 110 ]. These scientists have applied the AF − strain to the soil as infested grain cultures of barley, rice, or wheat, whereas [ 111 ] inoculated corn ears directly by injection.…”
Section: Efficacy Of Non-aflatoxigenic Strains As Biocontrol Agentsmentioning
confidence: 99%